Most important needs of family members of critical patients in light of the Critical Care Family Needs Inventory - Padilla Fortunatti, Cristóbal Felipe (Investigación y Educación en Enfermería, 2014)
Objective. This work sought to identify the most important needs for family members of adult critical patientsasdescribed in the literature pursuant to the dimensions established in the “Critical Care Family Needs Inventory” (CCFNI) by Molter and Leske. Methodology. A literature review was carried out by using the CCFNI instrument. The databases used were: Pubmed, CINAHL, Proquest Nursing & Allied Health Source, Proquest Psychology Journals, LILACS, Science Direct, Ovid SP, PsyicINFO, and SciELO. The following limitations for the search were identified: adult patients, articles in English and Spanish, with abstract and complete text available and which had been published from 2003 to June 2013; 15 articles were included. Results. The family’s hope on desired results and sincere communication with the healthcare staff turned out to be the most relevant needs, while the least important were related to comfort and having support structures or systems. Most of the studies were conducted in Asia and North America revealing differences in the order of importance assigned to each necessity. Certain sociodemographic and cultural characteristics impact upon how family members rank their needs; this also occurs with the nature of the most important needs for the family and the factors determining their prioritization. Conclusion. The articles included in this review mention the frequent interaction with the family and their holistic view of the person beyond the illness, determine that nurses are the most appropriate professionals to know and satisfy the family needs of critical patients.